Dimeric sesquiterpenoid-4H-chromone derivatives from agarwood of Aquilaria crassna and their cytotoxicity. (January 2018) - Yang, Yang; Chen, Hui-Qin; Kong, Fan-Dong; Zhou, Li-Man; Li, Wei; Dong, Wen-Hua; Chen, Zhi-Bao; Mei, Wen-Li; Dai, Hao-Fu
Abstract: Six previously undescribed uncommon ester-bonded dimeric compounds (aquilacrassnins A–F) containing a sesquiterpenoid and a 5, 6, 7, 8-tetrahydroxy-2-(2-phenylethyl)-5, 6, 7, 8-tetrahydro -4 H -chromone units were isolated from the EtOAc extract of agarwood originating from Aquilaria crassna . Their structures were elucidated by spectroscopic (NMR, UV, IR, MS, and ECD) methods. All the compounds were tested for AChE inhibitory activity and cytotoxicity against K562, BEL-7402, SGC-7901, Hela, and A549 tumor cell lines. The results showed that aquilacrassnin A, B, and E exhibited weak cytotoxicity against the five tested cell lines, whereas all the compounds were inactive against AChE. Graphical abstract: Phytochemistry investigations on Aquilaria crassna originated agarwood led to the isolation of six previously undescribed dimeric sesquiterpenoid-4 H -chromone derivatives. Image 1 Highlights: Six previously undescribed compounds were isolated from agarwood of Aquilaria crassna . The dimers of sesquiterpenoid-4 H -chromones are a relatively unusual class of chemical components. Aquilacrassnin A, B and E exhibited weak cytotoxicity against the tested cell lines.